An Analysis of Students’ Difficulties in TOEFL Reading: A Case Study - Al Fauzi, Fatih; Zahro, Zalifatus; Sabartono, Ribut (E-Link Journal, 2025)
The objective of this study is to determine to examine the challenges Islamic University of Jember students have when taking the TOEFL, particularly with regard to the reading comprehension portion of the exam. It used a qualitative research approach and case study design. In-depth interviews, close observation, and documentation of the teaching and learning process were used for collecting data. The analysis's findings indicate that UIJ students have a number of challenges while trying to comprehend reading texts, such as a restricted vocabulary, trouble with complicated sentence patterns, and lack of reading strategies. This study sheds light on the variables that prevent students from performing as well as they could on the TOEFL exam. The findings are expected to that the results of this study will help shape the TOEFL learning experience at UIJ and offer valuable insights that instructors can utilize to create more impactful lesson plans.